Oral manifestations of covid-19: review of the literature - Leite, Pryscilla Batista; Coelho, Andressa da Silva; Rio, Maria Ivanda; Freire, Nathalia Almeida; Ramos, Maria Eliza Barbosa; Israel, Monica Simoes (Journal of Oral Diagnosis, 2021)
COVID-19 is caused by the SARS-CoV-2 virus and proved to be a challenge since there was little knowledge about this disease. Several viral infections can affect the oral cavity and because of this is fundamental the study of this disease and whether oral manifestations could appear in an oral cavity. This work aims to review the literature on what is in the scientific articles of the oral manifestations of COVID-19 since the recognition of the existence of the pandemic.